Management of Identity and Access in the Cloud - Kashif Kifayat; Sameeh Abdulghafour Jassim; Sufyan T. Faraj (مجلة جامعة الانبار للعلوم الصرفة, 2012)
Cloud computing is new technology that provides cheaper, easier, and more powerful processes to customers over internet. The cloud service provider (CSP) provides virtualized resources on Internet instead of using software or storage on a local computer. The economic benefits are the main reason for using cloud computing. Cloud computing dynamically delivers everything as a service (XaaS) over the internet based on user demand, such as network, operating system, storage, hardware, software, and resources. Thus, many security and privacy issues must be taken into consideration. The services of cloud computing are usually classified into three types: Infrastructure as a Service (IaaS), Platform as a Service (PaaS) and Software as a Service (SaaS). This paper aims to achieve two main goals. The first is to review the field of cloud computing with an emphasis on the identity and access management (IAM) in the cloud. Secondly, we will report on our ongoing work for developing a novel system for IAM based on the techniques of Identity-Based Cryptography (IBC) security mediated cryptography. The proposed system architecture will be outlined along with some of the major operational steps.